Investigation of the unique metabolic fate of ethyl (6R)-6-[N-(2-chloro-4-fluorophenyl)sulfamoyl]cyclohex-1-ene-1-carboxylate (TAK-242) in rats and dogs using two types of 14C-labeled compounds having different labeled positions - Fumihiro, Jinno; Masaaki, Kakehi; Toshiyuki, Takeuchi; Yoshihiko, Tagawa; Takahiro, Kondo; Satoru, Asahi (Arzneimittelforschung, 2011)
The pharmacokinetics of TAK-242 (ethyl (6R)-6-[N-(2-chloro-4-fluorophenyl)sulfamoyl]cyclohex-1-ene-1-carboxylate, CAS 243984-11-4) and its metabolites were investigated in rats and dogs after intravenous (i. v.) dosing of TAK-242 using two types of radiolabeled TAK-242: [phenyl ring-U-14C]TAK-242 and [cyclohexene ring-U-14C]TAK-242.The phenyl ring moiety of TAK-242 yielded 2-chloro-4-fluoroaniline, M-I, and M-I was further acetylated and conjugated to formM-II and the glucuronide (M-I-G), respectively. M-I was also converted to M-III and M-IV by hydroxylation and subsequent sulfate conjugation. Meanwhile, the cyclohexene ring moiety of TAK-242 was metabolized to glutathione conjugate, M-SG, followed by further metabolism of M-SG to formcysteine conjugate (M-Cys) and mercapturic acid conjugate (M-Mer). After i. v. injection of [phenyl ring-U-14C]TAK-242 to rats and dogs, the 14C concentrations in dogs declined slowly with a half-life of about 1 week although that in rats was about 6 h. The predominant components in the plasma of rats and dogs were M-I-G and M-III, respectively. After i. v. injection of [cyclohexene ring-U-14C]TAK-242 to rats and dogs, 14C-components unextractable by organic solvents were observed in the plasma.These results indicated two unique metabolic fates of TAK-242. The phenyl ring moiety of TAK-242 showed species differences between rats and dogs in the metabolismand excretion kinetics and the cyclohexene ring moiety of TAK-242 showed potential for covalent binding to endogenous components such as plasma proteins.
Keywords: Anti-sepsis drug; Covalent binding; Metabolism; Pharmacokinetics; Species difference; TAK-242